Determination of oxonium ion and application via quenching of continuous fluorescence light (fluorescein salt) using I- -IO3--H3O+ system - Turkey Al-Awadie , Nagam S.; Kadhim Al-banaa , Marwa A. (Iraqi Journal of Science, 2023)
The research work present a sensitive, accurate and fast developed for the determination of oxonium ion (HCl, H2SO4 , HClO4 and tartaric acid). It relies on the formation free iodine molecule from the I--IO3--H3O+ reaction which react with fluorescein sodium salt solution causing to quench the fluorescence light (continuous fluorescence) when irradiated by laser source at 405nm. Optimum parameters were studied giving to specify the chemical and physical parameters. Two line manifold was used. The flow rate of 1.3 and 1.5 mL/min was used, 35μL sample volume no.1 and sample volume no.2 , linear dynamic range extend from 0.05-7, 0.05-7, 0.1-10 and 0.1-10 mMol.l-1 with correlation coefficient of 0.9933, 0.9964, 0.9984 and 0.9973 for HCl, H2SO4 , HClO4 and tartaric acid respectively. Using t-test it was shown that there was no significant difference between two methods (adopted and classical method) for both acid at 95% confidence level.